Bright skies and dark horses - Nesbitt, John D. (Waterville, Maine Five Star, 2023)
"These eight stories range in length from flash fiction to novella. In "Incident at Blue Nose Creek," an investigator pursues a suspect for the serial murders of three saloon girls. In "Visitors in Cantera," the narrator receives a visit from questionable relatives. In "In the Breaks," a girl goes deer hunting with her grandfather and has to fend off unwelcome advances from a young man. In "Man of Trees," a homesteader helps solve the murder of an old hobo. In "Night Horse," a man is killed when his plan to avenge his brother's death is thwarted, and the narrator has to fight for his life. In "Darkness in Burnett," the main character leaves Burnett, but his conscience compels him to return and help find the killer. In "Buckskin Ruby," a flashy stranger goes to work for a grading crew and exposes a murderer. In "Next to the Last Chance," a ranch hand wants to get out of the criminal way of life, as does the gang leader's woman, but the odds are against them"--
111446
Keywords: Western stories; Murder -- Fiction; Investigations -- Fiction; Gunfights -- Fiction; Ranches -- Fiction; Outlaws -- Fiction; Detective and mystery stories; Short stories; Western fiction; Nouvelles